PEMBANGUNAN KARAKTER DAN PEMBANGUNAN DIRI - Ida Bagus Gde Yudha Triguna (Pascasarjana Universitas Hindu Indonesia, 2015)
The pursuit of the education finds its ultimate result on the building of character and discipline. Both are the weapons to eclipse the ‘war’ of ideology within the world of education, i.e. between the positivism against the humanism. There are four characteristics in this regard: (1) the significance of the intelligence-creativity-inovation-reflection; (2) the enforcement of spirituality and ethics; (3) being appreciative, tolerant, and care one another; and (4) having sense of helpfulness and physical exercise.